Persistent Dento-Alveolar Pain Disorder: The Patient You Will Never Forget… - Cervantes-Chavarría DDS, Andrés (2016)
The Persistent Dento-Alveolar Pain Disorder (PDAP) is a neuropathic pain with a nonodontogenic etiology, difficult to diagnose and its usually accompanied by a growing anxiety from both the patient and also the dentist because of the multiple unsuccessful treatments performed attempting to relieve the pain. A thorough medical history, including complete clinical and radiographic examination and other relevant diagnostic tests, should aid the dentist to diagnose as early as possible, in order to start the indicated treatment for each case. The interdisciplinary management is recommended, as this condition usually involves psychosocial aspects of the patient, affecting his quality of life. Before performing any invasive clinical treatment, a responsible dentist should obtain a clear diagnosis of the etiology of the pain, and if in any doubt, always suspect of a nonodontogenic pain, such as the PDAP.